PERLINDUNGAN KONSUMEN DALAM KEPAILITAN - Salim, Rusnaldi (Unissula, 2020)
This study aims to provide an explanation of the consumer protection process in the event that business actors experience bankruptcy and the process of dispute resolution between producers and consumers against producers who fall bankrupt in realizing consumer protection in accordance with positive legal provisions in Indonesia. This study uses a Juridical Empirical Method. The results obtained from this study are the process of resolving consumer disputes in the event that a business actor goes bankrupt based on positive law in Indonesia can be pursued using the litigation and non-litigation channels. Settlement through non-litigation channels is carried out by means of Mediation, Conciliation and Arbitration. The responsibility of the company / business actor towards consumers if the company has been declared a fraud, namely by paying compensation in accordance with a written agreement that has been agreed by both parties. This step was taken to achieve consumer protection.